Synthesis and Computational Study of Bis-(1-(3-Chlorobenzoyl)-3-Phenylthiourea) Cobalt (III) as Anticancer Candidate - Ruswanto Ruswanto; Nisa Uswatun Khasanah; Gatut Ari Wardani; Richa Mardianingrum (Jurnal Kimia Sains dan Aplikasi, 2023)
Cancer is a disease characterized by cells forming abnormally so that a buildup can cause lumps. Drug compounds used for anticancer treatment by chemotherapy become a severe problem because they have dangerous side effects and can affect patient’s quality of life. This study aims to discover new drug compounds with lowered toxicity effects. This was achieved by modifying their structures through synthesis, characterization, and estimating the interactions of the synthesized compounds with specific target receptors, utilizing a docking method. The result obtained was a synthesis yield of 36.2%. The characterization of complex compounds was characterized by the presence of a maximum wavelength of 273 nm and a molecular weight of 652 g/mmol, indicating the absorption of Co-O and Co-S at respective wavenumbers of 498 cm-1 and 604 cm- 1. The docking results showed that the Bis-(1-(3-Chlorobenzoyl)-3-Phenylthiourea) Cobalt (III) complex had the best activity on human estrogen receptor alpha (hER alpha) with a binding affinity value of - 9.40 kcal/mol and an inhibition constant of 0.129 M, which was lower than the comparison compound (cisplatin) and had a better pharmacokinetic profile than cisplatin. This study shows that the Bis-(1-(3-Chlorobenzoyl)-3-Phenylthiourea) Cobalt (III) complex is predicted to have potential as an anticancer candidate.